2005
DOI: 10.1177/000992280504400108
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effectiveness of Biofeedback in Children with Dyssynergic Defecation and Recalcitrant Constipation/Encopresis: Does Home Biofeedback Improve Long-Term Outcomes

Abstract: The purpose of this study was to determine whether biofeedback benefits children with dyssynergic defecation and constipation/encopresis, and whether home biofeedback improves long-term outcomes. Thirty-six patients with chronic constipation who had failed at least 6 months of conventional treatment and demonstrated dyssynergic defecation at anorectal manometry were randomized to biofeedback in the laboratory alone (group 1, n=24) or in the laboratory and at home (group 2, n=12) and followed up at 2, 4, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…In contrast to an earlier study by the same group [68] in children with constipation with pelvic floor dyssynergia, it was shown that 76% of these children improved pelvic floor dyssynergia with biofeedback training but that only 48% of these children clinically recovered [71]. A more recent study showed similar success rates comparing home biofeedback to biofeedback in the laboratory [72].…”
Section: Biofeedbackmentioning
confidence: 61%
See 1 more Smart Citation
“…In contrast to an earlier study by the same group [68] in children with constipation with pelvic floor dyssynergia, it was shown that 76% of these children improved pelvic floor dyssynergia with biofeedback training but that only 48% of these children clinically recovered [71]. A more recent study showed similar success rates comparing home biofeedback to biofeedback in the laboratory [72].…”
Section: Biofeedbackmentioning
confidence: 61%
“…It was also decided to adopt the term fecal incontinence instead of the terms encopresis and soiling. With 84% of constipated children suffering from this complaint [3], www.elsevier.com/locate/pateducou Patient Education and Counseling 67 (2007) [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] the involuntary passing of fecal material in the underwear is one of the major features of childhood constipation.…”
Section: Introductionmentioning
confidence: 99%
“…This finding could not be explained by concomitant physical problems or comorbidities, as the number of these children was low and did not differ significantly between healthcare settings. Dysfunction of the pelvic floor muscles (PFM) and cooperating abdominal muscles is an integral component of the pathophysiology of CBBD [4547]. Only Chase et al [48] have examined whether different trunk musculoskeletal characteristics might be related to defecation difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of family educational interventions to address parental misconceptions such as believing that constipation is caused by a physical disorder or that the child is having accidents on purpose is also recommended (Philichi, 2008;van Dijk et al). Other treatment approaches that have been reported in the literature with varying results include biofeedback, hypnosis, reflexology, and Internet-based educational programs (Bishop, McKinnon, Weir, & Brown, 2003;Croffie et al, 2005;McGrath et al;Ritterband et al, 2003;Thomson, 2007).…”
Section: Treatment Approachesmentioning
confidence: 99%